Generasi Muda Dan Nilai-Nilai Perjuangan Bangsa - Sutanto, Djoko (Universitas Surakarta, 2011)
Abstract Younger generation in many countries play an important role in spearheading the movement changes. Therefore, youth contribution to the existence of the state is an extremely valuable contribution in development. In many regimes in some countries including Indonesias youth are often embraced in order to reinforce his power, but sometimes it is to muzzle the idealism of youth and fade values ââof national struggle. Youth movement in Indonesia has shown real evidence in contributing to the establishment of the independence of Indonesia. The emergence of youth organizations in the era of colonial rule shows that youth is a precursor for pioneering the movement toward independence. By using modern youth organizations were finally able to realize their idealism for the establishment of the independence of Indonesia. Key words: youth, the values ââof national struggle.